GENERALIZED MODEL OF THE ACTUAL WORK OF DECIDOUS AND CONIFEROUS WOOD UNDER AXIAL COMPRESSION ALONG THE FIBERS (Collection of scientific works «Modern structures of metal and wood», 2023)
Elements and structures made of wood have repeatedly proven their advantages over analogues made of metal and reinforced concrete. At the same time, materials, parts, elements and structures made of wood need additional experimental and theoretical studies to establish the actual mechanical characteristics of the material. That is, analysis with subsequent modeling of the work of wood as a material from the beginning of loading to its complete destruction. Most of the experimental studies of solid wood were carried out in the so-called "soft" test mode, that is, the work of such material was analyzed only up to a certain point of the ascending branch  of  the  "σ-u"  diagram  (according  to  the  increase  in  loads),  which  did  not  allow  us  to accurately study the strength and deformable characteristics on top of this chart, not to mention its descending branch. Since  the  end  of  the  last  century,  scientists  from  different  countries  began  to  conduct experimental  studies  of  materials  in  the  so-called  "hard  mode"  (increasing  displacements)  on modern servo-hydraulic and electromechanical testing machines, which  made it possible to build diagrams from the beginning of loading to the complete destruction of the material. The purpose of the work is to develop a theoretical model for the operation of hardwood and coniferous  wood  under  axial  compression  along  the  fibers  with  a  short-term  load  from  the beginning of loading to the complete destruction of the material, regardless of the age of the wood and humidity. A  generalized  model  of  the  actual  work  of  hardwood  and  coniferous  wood  under  axial compression along the fibers by a short-term load is proposed. Four characteristic areas of wood work were established (two on the ascending branch and two on the descending one). A theoretical definition  of  the  main  strength  and  deformation  parameters  of  the  complete  wood  deformation diagram is proposed. An approximating function has been established - this is a polynomial of the 4th  degree,  which  sufficiently  describes  the  deformation  diagram.  Methods  for  determining  the critical  and  limiting  deformations  of  wood,  the  initial  modulus  of  elasticity  and  the  modulus  of deformations are proposed.